EDUKASI KESEHATAN TERNAK BERDASARKAN PRINSIP KESEJAHTERAAN HEWAN UNTUK MENCEGAH WABAH PENYAKIT AFRICAN SWINE FEVER DAN PENYAKIT MULUT DAN KUKU - Cynthia Dewi Gaina; Filphin Adolfin Amalo; Fhady Risckhy Loe; Yustinus Oswin Primajuni Wuhan; I Gede Semarabawa; Jayusman Arsiyanti Joesoef (Universitas Nusa Cendana, 2022)
The emergence of African Swine Fever (ASF) and Food and Mouth Diseases (FMD) or PMK outbreaks encourages the importance of educating and raising awareness about the importance of a clean and healthy lifestyle in breeder farm through biosecurity application. In addition, the community needs to know with certainty the transmission and prevention of ASF so that it does not become more vulnerable. The purpose of this community service activity is to provide a scientific picture and be easily understood by the community at Mata Lombu Village, to anticipate the outbreak of the ASF and FMD disease. The activity stage was designed and was preceded by coordination and communication with the Mata Lombu village. Preparation intended is the determination of the direction and target of activities, activity models, follow-up activities and locations of activity concentration. The results of this activity are very in accordance with the expected, namely the people who were present actively asking about the material provided. This shows that their great curiosity and high attention of participants to increase their knowledge about how to prevent and deal with ASF and FMD and how to maintain good personal and environmental health.